Chronic high-fat diet induces overeating and impairs synaptic transmission in feeding-related brain regions - Wang, Xu; Li, Haohong (Frontiers in Molecular Neuroscience, 2022)
Obesity is linked to overeating, which can exacerbate unhealthy weight gain. However, the mechanisms for mediating such linkages are elusive. In the current study, we hypothesized that synaptic remodeling occurs in feeding-related brain regions of obese mice. To investigate this, we established a high-fat diet (HFD)-induced obese mouse model and observed that these mice consumed excessive calories. The effect of chronic HFD feeding on lipid droplet accumulation in different brain structures was also investigated. We found that lipid droplets accumulated on the ependyma of the third ventricle (3V), which is surrounded by key areas of the hypothalamus that are involved in feeding. Then, the spontaneous synaptic activity of miniature excitatory postsynaptic current (mEPSC) and miniature inhibitory postsynaptic current (mIPSC) was recorded in these hypothalamic areas. HFD induced a decreased amplitude of mEPSC in the arcuate nucleus (ARC) and the ventromedial hypothalamus (VMH), meanwhile, increased the frequency in the VMH. In addition, HFD reduced the frequency of mIPSC in the lateral hypothalamus (LH) and increased the amplitude of mIPSC in the paraventricular nucleus of the hypothalamus (PVH). Subsequently, we also measured the synaptic activity of nucleus accumbens (NAc) neurons, which play a vital role in the hedonic aspect of eating, and discovered that HFD diminished the frequency of both mEPSC and mIPSC in the NAc. These findings suggest that chronic HFD feeding leads to lipid accumulation and synaptic dysfunction in specific brain regions, which are associated with energy homeostasis and reward regulation, and these impairments may lead to the overeating of obesity.